2016
DOI: 10.1097/shk.0000000000000516
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Fenoldopam on Renal Function and Metabolism in an Ovine Model of Septic Shock

Abstract: In this model of septic shock, fenoldopam did not improve renal blood flow, worsened microcirculatory alterations, and induced metabolic changes that were indicative of increased glycolysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 37 publications
2
2
0
Order By: Relevance
“…We recently reported that the administration of fenoldopam in our ovine model of experimental septic shock failed to preserve RBF or improve renal function [39]. In the present study, acute denervation caused an increase in cortical perfusion and a doubling of RBF in the early phase of sepsis.…”
Section: Discussionsupporting
confidence: 43%
“…We recently reported that the administration of fenoldopam in our ovine model of experimental septic shock failed to preserve RBF or improve renal function [39]. In the present study, acute denervation caused an increase in cortical perfusion and a doubling of RBF in the early phase of sepsis.…”
Section: Discussionsupporting
confidence: 43%
“…In a recent study by our group in the same model as the present study, renal hypoperfusion was associated with an increase in the lactate-to-pyruvate ratio in the renal cortex, suggesting the presence of anaerobic lactate production (52). Also in this model, administration of the selective dopamine-1 receptor agonist fenoldopam did not preserve RBF (53). Moreover, in animals that received the drug at high-dose, RBF was lower after 18 h of sepsis than in control animals.…”
Section: Discussionsupporting
confidence: 50%
“…Porcine models with generalized atherosclerosis exist, but the animals do not appear to display any arterial hypertension (47,68). Therefore, we decided to test our hypothesis in the ovine model regularly used by our group (27,53). This does mean, however, that our results may lack some external validity, and studies that account for vascular comorbidity are necessary before any clinical recommendations can be made.…”
Section: Discussionmentioning
confidence: 99%
“…50 Recent work by our group showed that the selective dopamine-1 receptor agonist, fenoldopam, was ineffective at preserving RBF in a sheep model of septic shock. 51 Interventional clinical studies. Several small, nonblinded, interventional studies in human septic shock have reported a beneficial effect on urine output [52][53][54] and creatinine clearance [55][56][57] when using norepinephrine to increase RPP (Table 3).…”
Section: Systemic Hemodynamics Rbf and Kidney Functionmentioning
confidence: 99%